The influence of paediatric HIV infection on circulating B cell subsets and CXCR5+ T helper cells. (6th May 2015) - Bamford, A.; Hart, M.; Lyall, H.; Goldblatt, D.; Kelleher, P.; Kampmann, B.
Summary: Antiretroviral therapy (ART) only partially restores HIV‐induced alterations in lymphocyte populations. We assessed B and T cell phenotypes in a cohort of children from a single centre in the United Kingdom with perinatally acquired HIV compared to healthy controls. The majority of HIV infected children (44 of 56) were on fully suppressive combination ART. Children with perinatally acquired HIV had significantly lower memory B and CD4 + CD45RO + CXCR5 + [follicular T helper cell (Tfh)‐like] T cell percentages. Detectable viraemia was associated with higher CD21 – (activated and exhausted/tissue‐like memory) B cells. A greater proportion of life spent on suppressive ART was associated with higher memory B cell percentages. These results suggest that early and sustained suppressive ART may preserve B and T cell phenotypes in perinatally acquired HIV and limit deficits in humoral immunity. A lower proportion of circulating Tfh‐like cells in HIV infected children appears to be independent of HIV treatment history and ongoing HIV viraemia and warrants further investigation.